2003
DOI: 10.1021/bm034247a
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Ring Opening Polymerization of Lactones for Biomedical Applications

Abstract: Aliphatic polyesters prepared by ring-opening polymerization of lactones are now used worldwide as bioresorbable devices in surgery (orthopaedic devices, sutures, stents, tissue engineering, and adhesion barriers) and in pharmacology (control drug delivery). This review presents the various methods of the synthesis of polyesters and tailoring the properties by proper control of molecular weight, composition, and architecture so as to meet the stringent requirements of devices in the medical field. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
1,281
0
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 1,479 publications
(1,350 citation statements)
references
References 356 publications
15
1,281
0
12
Order By: Relevance
“…Zhang et al 68,69 reported similar observations with aluminum complexes of functionalized phenolate ligands, which he interpreted to arise from higher reaction temperatures resulting in transesterification. [70][71][72] However, it could also be that when 4 and 5 are used, initiation proceeds via acid-initiation (HCl generated in situ from adventitious water) and this reaction is more uncontrolled than in reactions catalyzed by an Al-alkyl/alcohol system. Another possibility is that the reaction may be proceeding via a reaction pathway involving insertion of the monomer into the Al-Cl bond.…”
Section: Ring-opening Polymerization Of ε-Caprolactonementioning
confidence: 99%
“…Zhang et al 68,69 reported similar observations with aluminum complexes of functionalized phenolate ligands, which he interpreted to arise from higher reaction temperatures resulting in transesterification. [70][71][72] However, it could also be that when 4 and 5 are used, initiation proceeds via acid-initiation (HCl generated in situ from adventitious water) and this reaction is more uncontrolled than in reactions catalyzed by an Al-alkyl/alcohol system. Another possibility is that the reaction may be proceeding via a reaction pathway involving insertion of the monomer into the Al-Cl bond.…”
Section: Ring-opening Polymerization Of ε-Caprolactonementioning
confidence: 99%
“…The synthesis of novel polymer structures through ring opening polymerization (ROP) has been studied for several years [27][28][29] and is the most popular route for poly(α-ester) synthesis. One of the most important factors that influences the properties of aliphatic polyesters is the molecular weight, with high molecular weight materials generally having better mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers and various copolymer compositions have shown considerable potential as effective drug carriers [41,42] and have been extensively studied for the controlled release of drugs due to their tunable degradation rates (from months to years), wide range of mechanical properties and biodegradability [40,[43][44][45][46][47][48][49]. Poly(l-lactide) (PLLA) is particularly advantageous since its degradation product, lactic acid, is well tolerated by the body [50][51][52][53]. The degradation properties of polyesters have been widely studied [54,55] and are known to be affected by polymer properties (i.e., molecular weight, chemistry, wettability and crystallinity) and also the properties of the release medium (i.e., pH, ionic strength and solvent) [56].…”
mentioning
confidence: 99%